KONSUMSI TABLET FE DENGAN KEJADIAN KONSTIPASI PADA IBU HAMIL TRIMESTER II DAN III - Lilik Rosdewati (Jurnal Keperawatan Priority, 2022)
Iron is an essential nutrient needed by every human cell. Constipation or constipation is a condition that is difficult or unable to defecate, feces (feces) the feeling of defecation is not complete, or infrequent bowel movements. Relationship between Fe tablet consumption and constipation incidence in pregnant women trimester II and trimester III at Yusniar Clinic Pangkalan Brandan in 2019. This study uses an analytical method with a cross-sectional design. The population in this study was pregnant women and the sample of this study used a saturated sampling so that a sample of 30 pregnant women could be used. The study the majority of mothers who consumed Fe tablets were 28 people (87%) and the minority did not consume Fe tablets as many as 2 people (13%). The mothers who consumed Fe tablets who experienced constipation, the majority were 27 respondents (90%,) and the mothers who consumed Fe tablets who did not experience constipation were a minority of 1 respondent (10%). The results showed that there was a relationship between the consumption of Fe tablets and the incidence of constipation, with a p-value of 0.004.  It is hoped that all pregnant women take Fe tablets together with drinking enough water, consuming fiber-rich foods, regular exercise, and adequate rest so as not to experience constipation when consuming Fe tablets and following health education conducted by local health workers and following classes for pregnant women on a regular basis.